Computer Problem Solver (CoPS) method for teaching first year computer programming course / Roslan Sadjirin ... [et al.] - Sadjirin, Roslan; Noradzan, Haslinda; Alias, Nursyahidah; Ismail, Nor Zalina; Abd Aziz, Mohd Norafizal; Md Raus, Mohd Ikhsan; Abd Aziz, Muhd Eizan Shafiq; Zakariah, Zazaleena; Hussain, Fazlin Marini; Ismail, Siti Nurbaya; Hashim, Norhafizah (2011)
Poor rates of result among Computer Science students at Universiti Teknologi MARA (UiTM) Pahang in computer programming course has caused the performance, competency level as well as the student learning outcome be at par, thus affecting the KPI 's performance of the Computer Science Department. In order to overcome this problem, an improvisation of the teaching and learning method is introduced and implemented. This paper presents the introduction of the teaching and learning method called CoPS (Computer Problem Solver) which has been used and implemented for teaching computer programming course among computer science students in their first year at UiTM Pahang. There are four batches of students starting from 2009 until 2011 that are involved in this study. Analysis shows that there is significant improvement in the students' performance after using CoPS method the first computer programming course.